Un médiévalisme scolaire : le traitement de la période médiévale dans les manuels scolaires de classe de seconde, édition 2019 - Florian Besson (Bulletin du Centre d’Études Médiévales d’Auxerre)
The new high school history programs, which came into effect in September 2019, require a chapter devoted to the study of the medieval Mediterranean in the tenth grade. As with every curriculum reform, school textbook publishers have published new textbooks. This article analyzes the representations of the medieval period in these seven textbooks, via an analysis quantitative and qualitative. Textbooks can be considered as one way to built and to diffuse a school medievalism, in other words a certain representation of the medieval period transmited to a public of high school student.